EVALUATION OF ANALGESIC AND ANTI INFLAMMATORY ACTIVITIES OF PORANA PANICULATA WHOLE PLANT - SANJEEVA KUMAR A; RAVEENDRA REDDY J; RAMA MOHAN GUPTA V (International Journal of Pharma and Bio Sciences, 2014)
Porana paniculata is an ever green creeper belongs to family Convolvulaceae which is widely grown in tropical countries like India. Porana paniculata whole plant is used in ayurveda and folklore for treatment of various disorders including pain and inflammations. Present study was aimed to evaluate preliminary phytochemical studies and analgesic and anti-inflammatory activities of Porana paniculata whole plant. Plant material was subjected to extraction by maceration by using ethanol and water mixture as solvent and subjected to preliminary phytochemical screening. For Analgesic activity, hot plate, tail immersion and acetic acid induced writhing models were used where as for anti inflammatory activity, carrageenan and histamine induced model were employed. A thick green viscous matter about 28.9 gm was obtained from 1000 gm of plant material and the percentage was found to be 2.89% w/w. Preliminary phytochemical screening of whole plant of Porana paniculata revealed the presence of alkaloids, carbohydrates, saponins, tannins and flavonoids. In hot plate and tail immersion methods, plant extract showed significant increase in reaction time and it showed 50.09 % inhibition of the writhing caused by acetic acid (p<0.05). In anti inflammatory activity, plant extract showed 25.86, 43.10 % inhibition in carrageenan induced model and 13.41, 54.87 % inhibition in histamine induced model at its lower and higher dose levels respectively. From the above findings, it can be concluded that Porana paniculata whole plant possesses significant analgesic and anti inflammatory activities. Present study supports the folklore claim of the plant for pain and inflammation.